Observations on the growth of Penaeus monodon in a low saline culture pond - Guru, B C; Mohapatra, U C; Pal, S; Mohanty, A K (Indian Journal of Fisheries, 2011)
The shrimp Penaeus monodon grows to a good size with low saline water. A production of 172.2 to 512.1 kg/ha crop has been achieved (CMFRI 1988). Usually the saline level decreases in the tide water during monsoon. Attempts were made to study the growth of Penaeus monodon in a monoculture tide-fed pond of low saline water and to examine it9 viability, thereby exploring the possibilities of culturing this species in the potential areas where tide is the cheap water source